Childhood Socioeconomic Status and Adult Subjective Wellbeing: The Role of Hope and Sense of Control - Wang, Li; Li, Fenglan; Meng, Keqiang; Dunning, Kelly Heber (Frontiers in Psychology, 2022)
The study investigates the unexplored link between childhood socioeconomic status and adult subjective well-being using data from a field survey of 568 rural residents from poor areas in China. This study focuses on exploring the relationship between childhood socioeconomic status, hope, sense of control, and adult subjective well-being using a structural equation model. Results indicated that hope and sense of control mediated the links between childhood socioeconomic status and adult subjective well-being, revealing that hope and sense of control may buffer the negative impacts of childhood poverty experiences on subjective well-being. The findings provide new insights into the impacts of childhood socioeconomic status on adult subjective well-being and expand the literature on key factors in adult subjective well-being.